2010
DOI: 10.5799/ahinjs.01.2010.01.0004
|View full text |Cite
|
Sign up to set email alerts
|

Beta-human chorionic gonadotropin concentrations in cervicovaginal secretions as an early marker of preterm delivery

Abstract: ÖZETAmaç: Preterm doğum erken belirteci olarak serviko-vajinal sekresyonlardaki koriyonik gonadotropin'in rolünü araştırmak.Yöntemler: Bir önceki doğumu erken doğum veya ikinci trimester düşük öyküsü risk faktörü olan, 25-36 gebelik haftasına sahip 55 gebe çalışmaya alındı. Hastaların tü-münde servikovajinal sekresyonlardaki beta-insan koriyonik gonadotropin (β-hCG) düzeyleri radioimmunassay yöntemiyle ticari bir kit kullanılarak ölçüldü. Bulgular:Gebelerden 25'i preterm, 30'u term doğum yaptı. Term ve preterm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…33 Adhikari et al also concluded that cervicovaginal β-hCG may have a role in predicting preterm delivery both in symptomatic and asymptomatic women at high-risk for preterm delivery, but cut off value of β-hCG in their study was very low 14 mIU/ml for predicting delivery <34 week with sensitivity, specificity, positive and negative predictive value of 83.3%, 85.5%, 33.3% and 98.3% respectively, 4.75 mIU/ml for predicting delivery <37 week with sensitivity, specificity, positive and negative predictive value of 70%, 61.8%, 40% and 85% respectively as compared to present study. 34 Present study had comparable sensitivity and negative predictive value to Erdalsak et al, Mishra et al 9,35 They found a cut off value of 13.5 mIU/ml for cervicovaginal β-hCG for prediction of preterm delivery with sensitivity 71.1%, specificity 81.2%.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…33 Adhikari et al also concluded that cervicovaginal β-hCG may have a role in predicting preterm delivery both in symptomatic and asymptomatic women at high-risk for preterm delivery, but cut off value of β-hCG in their study was very low 14 mIU/ml for predicting delivery <34 week with sensitivity, specificity, positive and negative predictive value of 83.3%, 85.5%, 33.3% and 98.3% respectively, 4.75 mIU/ml for predicting delivery <37 week with sensitivity, specificity, positive and negative predictive value of 70%, 61.8%, 40% and 85% respectively as compared to present study. 34 Present study had comparable sensitivity and negative predictive value to Erdalsak et al, Mishra et al 9,35 They found a cut off value of 13.5 mIU/ml for cervicovaginal β-hCG for prediction of preterm delivery with sensitivity 71.1%, specificity 81.2%.…”
Section: Discussionsupporting
confidence: 65%
“…This sample was sent to laboratory immediately after collection. 9 The assay procedure began with centrifugation of the solution at 3500×g for 5 min to remove particulate matter. The remaining solution was quantitatively tested for the presence of β-hCG.…”
Section: Exclusion Criteriamentioning
confidence: 99%
See 2 more Smart Citations
“…such as cervical length measurement through transvaginal ultrasound, bacterial vaginosis tests, fetal fibronectin, hCG in cervical and vaginal secretions (5,6), maternal corticotropin releasing hormone (CRH) (7), and maternal serum alpha fetoprotein in 11-13 weeks (8), have been suggested to predict preterm delivery; however none of them are able to accurately identify cases at risk for preterm delivery and its related complications (9,10). Acute phase response is defined as the systemic response to inflammation and tissue damage that occurs within hours to days (11).…”
Section: Key Pointmentioning
confidence: 99%